Comparison of Effects of Volume-Controlled and Pressure-Controlled Ventilation during Laparoscopic Surgeries in Birat Medical College Teaching Hospital - Arjyal, Batsalya; Khanal, Kanak; Rajbanshi, Lalit Kumar; Bajracharya, Akriti; Regmi, Gunjan (Birat Journal of Health Sciences, 2022)
Introduction: The pneumoperitoneum created during laparoscopic surgery has numerous effects on the patient ranging from respiratory to hemodynamics. The two common methods of ventilator are volume control and pressure control. The volume control method has been commonly used during general anesthesia. Pressure control method has been used in intensive care unit for improving the respiratory mechanics. Objective: The study aims to compare the effects of pressure control to volume control ventilation in patients undergoing laparoscopic surgery. The hypothesis of the study is that pressure control method improves the respiratory mechanics by decreasing the peak airway pressure and increasing the lung compliance. Methodology: The total of 100 patients who underwent laparoscopic surgery were undertaken for this study. The 50 in each group (PCV and VCV) were allotted randomly. As per predicted body weight, the tidal volume was adjusted to 8 ml/kg, for both the modes of ventilation, peep 5 mm of Hg with fio2 of 100% and I:E-1:2,. The variations in peak airway pressure, mean airway pressure, lung compliance, SPO2 and hemodynamic parameters were observed at baseline (T1), at pneumoperitoneum (T2), after 10 minutes of pneumoperitonium (T3) and at 20 minutes after pneumoperitonium (T4). Results: The pressure control group on comparison to volume control mode group showed significant decrease in peak airway pressure while increase in mean airway pressure and increase in lung compliance at different points of pneumoperitoneum. However there was no significant change in hemodynamics between the two groups in patient undergoing laparoscopic surgery. Conclusion: We conclude that respiratory mechanics improve when the patient is on pressure control ventilation in compared to volume control method of ventilation. Whereas there is no difference in hemodynamic parameters between the two methods.